Relationship Between Enthusiasm for Online Gaming and Learning Motivation Among Students of Different Status - Kochetkov N.V; Volozhaeva E.N (Moscow State University of Psychology and Education, 2021)
The article answers the question how learning motivation and enthusiasm for online gaming are related in students with low, medium and high social status. We present results of a study conducted in 2020 that involved 104 students of 9-11 grades of Moscow schools, 41% (n=43) males, 59% (n=61) females. The techniques used in the study included the academic motivation scale, the assessment tool for game addiction, sociometry, the reference measurement technique, and the technique for identifying informal intragroup power structure in a contact community. The results show that each structure of the integral intragroup status is characterized by its own relationship between learning motivation and willingness to engage intensively in online gaming. As it was revealed, in the attraction structure of intragroup status among high-status students the game addiction indicator is negatively correlated to learning motivation, whereas in the structure of informal power among low-status students this correlation is positive.